A New Strategy for Korea's Fiscal Policy in a Low Growth Environment - Zoli, Edda.; Laxton, Douglas; Wang, Hou. (Washington, D.C. : International Monetary Fund, 2018)
Adverse demographics and other structural weaknesses impinge on Korea's long-term fiscal outlook and potential growth. Moreover, inadequate social protection is creating poverty and dampening consumption. The paper presents projections of Korea's fiscal outlook, using new estimates of potential growth obtained with a novel multivariate filter. It shows that keeping fiscal revenues-to-GDP constant would result in an explosive public debt dynamic in the long term. Then, through simulations of the Flexible System of Global Models, the paper analyzes policies to preserve fiscal sustainability, while boosting potential growth and social protection. It concludes that with greater revenue mobilization, Korea can stabilize debt-to-GDP well below 'dangerous' levels. Policies to address Korea's challenges include higher targeted transfers to the most vulnerable and fiscal measures to support female labor force participation and employment, accompanied by product and labor market reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet